Pelatihan Image Processing Untuk Meningkatkan Kemampuan Analisis Visual Data Bagi Dosen Kopertip Indonesia - Ahmad Rifa’i; Arif Rinaldi Dikananda; Aruka Wijaya; Muhammad Adhari Febriyan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This community service activity focuses on improving the competence of lecturers in the Indonesian Higher Education Cooperative (KOPERTIP) in the field of image processing and visual data analysis, with an emphasis on image preprocessing training. The background of this activity is the rapid development of information technology that demands a deep understanding of image processing for visual data analysis. Many lecturers, especially in KOPERTIP, still lack mastery of basic image preprocessing techniques, which hinders the optimal use of visual data in research and teaching. This training program aims to address this skill gap by providing lecturers with practical knowledge and skills in processing visual data using software such as Python with the OpenCV and PIL libraries. The training covers the basic concepts of image preprocessing, including image enhancement, noise reduction, edge detection, and image transformation techniques. The training method involves a combination of theory and direct practice, case studies, and intensive mentoring. The results of this activity include increased understanding and technical skills of lecturers, the compilation of training modules, draft scientific publications, and the formation of a learning and collaboration community among lecturers. The positive impacts include improved teaching quality, increased interest in visual data research, and the potential for broader academic collaboration. This activity is considered successful in improving the competence of KOPERTIP Indonesia lecturers in digital image processing, which is expected to enhance the quality of research, teaching, and the competitiveness of higher education institutions. The program emphasizes the importance of practice-based training, continuous mentoring, and the relevance of the material to the curriculum and academic research. Recommendations for program sustainability include advanced training, collaborative application development, facility improvement, and cooperation with related institutions or industries.